Genomic features and fitness cost of co-existence of blaKPC-2 and blaVIM-2 plasmids in ICU-derived pan-drug resistant Pseudomonas aeruginosa - Zheng, Lin; Wang, Zixian; Zhang, Xin; Lu, Gejin; Jing, Jie; Sun, Shiwen; Sun, Yang; Ji, Xue; Jiang, Bowen; Zhu, Lingwei; Guo, Xuejun (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroudThe emergence of carbapenem-resistant Pseudomonas aeruginosa (CRPA) co-producing KPC-2 and VIM-2 has increased the healthcare threats.ResultsIn this study, a CRPA strain 18102011, was isolated from the bile of a burn patient in ICU of China. Its whole genome was sequenced via the PacBio platform. The molecular characteristics of the genome were analyzed to assess the genetic environment of the carbapenemase genes blaKPC-2 and blaVIM-2. Antimicrobial susceptibility, plasmid stability, bacterial growth curves, and plasmid conjugation were measured. Strain 18102011 exhibited a resistant pattern to all 23 antibiotics tested, which could be defined as a pan-drug resistant P. aeruginosa strain. Two plasmids were identified in this strain: the IncpRBL16 mega-plasmid pP2011–1 carrying blaVIM-2 and the IncP6 plasmid pP2011–2 carrying blaKPC-2. blaVIM-2 was located in the region of In2057 (a novel class 1 integron) that was inserted into pP2011-1, and the expression of the blaVIM-2 gene was increased by the PcWTGN-10 promoter located at the 5’-CS. For the blaKPC-2 gene, the core module Tn3-ISKpn27-blaKPC-ΔISKpn6 served as the blaKPC-2 platform in pP2011-2, and the expression of the blaKPC-2 gene was achieved via the P1 promoter located downstream of ISKpn27. This expression pattern resulted in MICs of 4,096 μg/mL of imipenem for both strain 18102011 and its transconjugant D2011. Both plasmids were stable in strain 18102011 and could be co-transferred to other strains.ConclusionThis study raised concerns regarding the high stability and non-inferior fitness of blaKPC-2-blaVIM-2-CRPA, shed light on its genomic characteristics, and underscored the importance of continued surveillance of CRPA.